2008
DOI: 10.5194/bgd-5-2607-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methanotrophy potential versus methane supply by pore water diffusion in peatlands

Abstract: Abstract. Low affinity methanotrophic bacteria consume a significant quantity of methane in wetland soils in the vicinity of plant roots and at the oxic-anoxic interface. Estimates of the efficiency of methanotrophy in peat soils vary widely in part because of differences in approaches employed to quantify methane cycling. High resolution profiles of dissolved methane abundance measured during the summer of 2003 were used to quantify rates of upward methane flux in four peatlands situated in Wales, UK. Aerobic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…From the microcosm results, sequential use of electron acceptors occurs relatively quickly after rewetting (in the short-term; Table 5) tending to increase pH (see discussion below), in line with the general consensus (e.g. Blodau et al, 2004;Hornibrook et al, 2008;Toberman et al, 2008;Knorr et al, 2009), and evidence for this can be seen in the field too. In the long-term though, SO 4 2-accumulated markedly, the reasons for which are unclear but could include SO 4 2-release from the peat matrix via sulphatase activities (see later), more efficient thiosulphate recycling (Heitmann et al, 2007), or an inhibition of sulphate reduction by competing anaerobic processes (Paul & Clark, 1989).…”
Section: Discussionsupporting
confidence: 52%
“…From the microcosm results, sequential use of electron acceptors occurs relatively quickly after rewetting (in the short-term; Table 5) tending to increase pH (see discussion below), in line with the general consensus (e.g. Blodau et al, 2004;Hornibrook et al, 2008;Toberman et al, 2008;Knorr et al, 2009), and evidence for this can be seen in the field too. In the long-term though, SO 4 2-accumulated markedly, the reasons for which are unclear but could include SO 4 2-release from the peat matrix via sulphatase activities (see later), more efficient thiosulphate recycling (Heitmann et al, 2007), or an inhibition of sulphate reduction by competing anaerobic processes (Paul & Clark, 1989).…”
Section: Discussionsupporting
confidence: 52%
“…2, blue color). Several authors have reported positive correlation between CH 4 fluxes and CH 4 oxidation rates (Basiliko et al, 2007;Hornibrook et al, 2009). This may suggest that CH 4 oxidation is substrate (CH 4 )-dependent rather than limited by the availability of O 2 (Sundh et al, 1994;Saarnio et al, 1997).…”
Section: Effect Of Microform Types and Soil Depth On Co 2 Efflux Ch mentioning
confidence: 91%
“…Under water-logged and anoxic conditions (e.g., pristine and re-wetted peatlands), CH 4 is mainly produced by methanogens if other terminal electron acceptors are depleted, and oxygenated carbon compounds (e.g., CO 2 ) are available (Lyu et al, 2018;Gao et al, 2019). At anoxic to oxic interfaces, methanotrophic microbes can oxygenize CH 4 to produce energy and CO 2 (Hanson and Hanson, 1996;Hornibrook et al, 2009). These basic concepts of GHG production are also valid in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 98%